(untitled) (Ottawa, Canada, 1998)
The end of the Cold War was to usher in a new era of international peace and security. Instead, new types of conflicts have emerged and the international community has had to react quickly. New threats to peace have been countered with varying doses of peacemaking, peacekeeping, and, today, peace-building. This newest approach --- peace-building --- recognizes that the sources of violent conflict are complex and that human security and international stability will only be achieved by integrating political, military, and development efforts.
Keywords: Economic assistance,Hỗ trợ kinh tế; Political aspects,Developing countries,Khía cạnh chính trị,Các nước đang phát triển; Canada,Canada